2019
DOI: 10.5847/wjem.j.1920-8642.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Can an 8th grade student learn point of care ultrasound?

Abstract: BACKGROUND: Point-of-care ultrasound has gained widespread use in developing countries due to decreased cost and improved telemedicine capabilities. Ultrasound training, specifi cally image acquisition skills, is occurring with more frequency in non-medical personnel with varying educational levels in these underdeveloped areas. This study evaluates if students without a high school education can be trained to acquire useful FAST images, and to determine if an 8 th grade student can teach peers these skills. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A previous study by Vinayak et al was able to train midwives to utilize POCUS devices alongside mobile phones and tablets to capture high-enough resolution images to identify crucial features within images [79]. Similarly, Kwon et al found that the majority of eighth graders were able to obtain adequate POCUS (FAST) images, even with minimal training, emphasizing the effectiveness of training and the ease of use of POCUS as an imaging modality [80]. Although the ability to teach the layperson is extremely helpful, these past methodologies rely on the continuous assurance that everyday citizens remember this training.…”
Section: Implementation Of Pocus In Lrs and Barriersmentioning
confidence: 98%
“…A previous study by Vinayak et al was able to train midwives to utilize POCUS devices alongside mobile phones and tablets to capture high-enough resolution images to identify crucial features within images [79]. Similarly, Kwon et al found that the majority of eighth graders were able to obtain adequate POCUS (FAST) images, even with minimal training, emphasizing the effectiveness of training and the ease of use of POCUS as an imaging modality [80]. Although the ability to teach the layperson is extremely helpful, these past methodologies rely on the continuous assurance that everyday citizens remember this training.…”
Section: Implementation Of Pocus In Lrs and Barriersmentioning
confidence: 98%
“…Studies by Lee et al (2017) and Denny et al (2018) articulate the utility of ultrasound educational workshops taught by English-speaking medical students to providers in Indonesia and Tanzania (Lee et al , 2017; Denny et al , 2018). Because of the success of ultrasound education within medical education curriculums (Fox et al , 2014), efforts to integrate ultrasound into more creative settings, such as undergraduate and high school basic sciences curricula, have shown promising benefits as well (Kwon et al , 2019). Kwon et al (2019) described middle schoolers learning ultrasound and demonstrating an ability to obtain clinically adequate FAST ultrasound images after minimal training (Kwon et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the success of ultrasound education within medical education curriculums (Fox et al , 2014), efforts to integrate ultrasound into more creative settings, such as undergraduate and high school basic sciences curricula, have shown promising benefits as well (Kwon et al , 2019). Kwon et al (2019) described middle schoolers learning ultrasound and demonstrating an ability to obtain clinically adequate FAST ultrasound images after minimal training (Kwon et al , 2019). Thus, it has become apparent that with the right opportunities and skills, a variety of learners, regardless of training or experience, are capable of learning ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…In general, POCUS examinations are goal directed, which means that their purpose is not to perform a complete ultrasound examination, but to answer specific objective questions that the clinician has; these are often binary in nature, with ‘yes/no’ answers generated, rather than relying upon operator interpretation. This in turn means that acquisition of competency is quick (Kwon and others 2019, Burnotte and others 2020).…”
mentioning
confidence: 99%